Novel software developments for the automated post-processing of high volumes of velocity time-series. (November 2015) - Jesson, M.A.; Bridgeman, J.; Sterling, M.
Abstract: This paper describes novel software developments designed to automate the parsing, filtering (despiking) and calculation of mean flow and turbulence parameters of velocity time-series. The software was written to facilitate the processing of the large number of time-series (approximately 4000) generated by the authors' experimental work, mapping velocity and turbulence fields in a laboratory flume using an acoustic Doppler velocimeter. The software will import all, or selected, data files from a specified directory, despike them using one of a number of filters (Phase-Space Thresholding, for example) and graphically present the parameter distribution over the cross-section under investigation. Many different data file formats are supported, including Nortek binary formats, Turbulent Flow Instrumentation "Cobra" probe format and delimited plain-text files, meaning that the software has applications in a significant number of different environmental engineering applications where large data sets are routinely collected and analysed.